(untitled) (International Journal of Engineering and Computer Science, 2023)
This work provides an in-depth analysis of the impact of artificial intelligence (AI) in cybersecurity. With the rise of cybercrime and the increasing sophistication of cyberattacks, organizations are implementing advanced cybersecurity measures, and AI is emerging as a critical tool. The work discusses the benefits of AI in cybersecurity, including enhanced threat detection, reduced false positives, automation, improved response time, and predictive analytics. However, it also highlights the challenges associated with AI in cybersecurity, such as lack of transparency, bias, adversarial attacks, integration, and skill gap. The work concludes that AI is not a panacea for all cybersecurity problems, but it is a critical tool that can help organizations defend against ever-evolving cyber threats. Addressing the challenges associated with AI in cybersecurity requires ongoing monitoring and refinement to ensure that AI-powered cybersecurity solutions remain effective and secure. Finally, the work identifies ethical considerations and regulatory frameworks that organizations must consider when implementing AI in cybersecurity. Overall, this work provides valuable insights into the current state and future of AI in cybersecurity and highlights the importance of a holistic approach to cybersecurity.